Bias and Bias Correction Method for Nonproportional Abilities Requirement (NPAR) Tests. Issue 1 (13th March 2019) - Ip, Edward H.; Strachan, Tyler; Fu, Yanyan; Lay, Alexandra; Willse, John T.; Chen, Shyh‐Huei; Rutkowski, Leslie; Ackerman, Terry
Abstract: Test items must often be broad in scope to be ecologically valid. It is therefore almost inevitable that secondary dimensions are introduced into a test during test development. A cognitive test may require one or more abilities besides the primary ability to correctly respond to an item, in which case a unidimensional test score overestimates the primary ability and creates interpretability problems. In this article, we demonstrate the nonproportional abilities requirement, a phenomenon with which secondary abilities are more required for difficult items. A novel and practical method for correcting bias in the primary ability is proposed and illustrated using a real data set from an international assessment. Simulation data are also used to evaluate the performance of the method.